The School Principals' Leadership Style on Teacher Performance - Ayana, Riya Septi; Normuslim, Normuslim (International Journal on Advanced Science, Education, and Religion, 2025)
The school principal is not only tasked with managing administration, but also providing direction to educators and education staff to develop the school and improve the quality of teaching. Therefore, in this research, it is important to review the principal's leadership style on teacher performance. The method in this study uses a literature review. The findings in this research are that the school principal's leadership style or other language is a distinctive way or characteristic of leading a school. Each school principal is of course different in implementing his leadership style, but they both want to achieve the school's goals and vision. The principal's leadership style relates to the way or characteristics of a leader in managing, guiding and directing teachers to achieve educational goals. Leadership styles such as self-criticism, democracy, instructive, consultative, delegative, participative, transformational, situational and transactional, of course each leadership style has its strengths and weaknesses, so it needs to be appropriate to the conditions and situation. The principal's leadership style has an influence on teacher performance and the success or failure achieved.